No Residual Basal Cell Carcinoma after Excision for Biopsy-proven Tumor: Clinical and Medicolegal Implications - Raffi Gurunluoglu, MD, PhD, FACS; Eddie Kubek, MD; Jamie Arton, PA-C; Adam Olsen, DDS; Michael Bronsert, PhD, MS (Plastic and Reconstructive Surgery, Global Open, 2013)
Summary: Our analysis of 127 head and neck region basal cell carcinomas (BCCs) showed that there was no evidence of residual BCC in 15% of patients, one of which is presented in this report. These patients received some type of reconstructive surgery after excision of lesions with negative tumor. Thus, there is a chance that any reexcision after a shave biopsy which is positive for BCC may be negative for tumor. This finding substantiates our realization that sometimes what some would call unnecessary surgery is a common reality. The surgeon’s goal is tumor eradication, and therefore, watchful waiting is usually not a legitimate clinical implication. This report has value in letting our esteemed legal colleagues know what we do not know, which still remains within the standard of appropriate care. However, the finding of no residual tumor in the current report may change our practice habits. Watchful waiting may be an option, particularly in the elderly and fragile patients. Also, one may opt to decrease the safety margins during excision when treating patients with biopsy-proven BCC. However, reconstructive procedures may still be required in the case of nonpersistent tumor. Therefore, it is extremely important that the informed consent should include statements regarding possible reconstructive procedures to avoid medicolegal implications.